2018
DOI: 10.1371/journal.pone.0198608
|View full text |Cite|
|
Sign up to set email alerts
|

Characterization of kidney CD45intCD11bintF4/80+MHCII+CX3CR1+Ly6C- “intermediate mononuclear phagocytic cells”

Abstract: Kidney immune cells play important roles in pathogenesis of many diseases, including ischemia-reperfusion injury (IRI) and transplant rejection. While studying murine kidney T cells, we serendipitously identified a kidney mononuclear phagocytic cell (MPC) subset characterized by intermediate surface expression of CD45 and CD11b. These CD45intCD11bint MPCs were further identified as F4/80+MHCII+CX3CR1+Ly6C- cells, comprising ~17% of total CD45+ cells in normal mouse kidney (P < 0.01) and virtually absent from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 40 publications
1
16
0
Order By: Relevance
“…The reason for this discrepancy is derived from the difference in tissue monocyte-lineage of the depleted macrophage subtypes by the above two tools 42,43 . In our study, we found that CLs depleted most of Ly6C − macrophages and a small portion of Ly6C + macrophages, which is consistent with a recent study 44 . However, the relation between these subtypes is still unclear and further studies will be required for more precise depletion of macrophage subtypes.…”
Section: Discussionsupporting
confidence: 93%
“…The reason for this discrepancy is derived from the difference in tissue monocyte-lineage of the depleted macrophage subtypes by the above two tools 42,43 . In our study, we found that CLs depleted most of Ly6C − macrophages and a small portion of Ly6C + macrophages, which is consistent with a recent study 44 . However, the relation between these subtypes is still unclear and further studies will be required for more precise depletion of macrophage subtypes.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have administered higher doses of clodronate multiple times to achieve complete macrophage depletion 32 34 . In our model, liposomal clodronate at a single intraperitoneal dose of 200 ul significantly reduced blood monocytes (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate the phenotype and function of donor rMFs after reversible I/RI, we used a model of congeneic renal transplantation. Compared with models of I/RI obtained by clamping the renal artery, 33,44 this method allowed us to discriminate between renal mononuclear-phagocytes from the donor and those derived from recipient monocytes infiltrating the graft at reperfusion.…”
Section: Discussionmentioning
confidence: 99%